Financing of Cultural Institutions by Local Government Units on The Example of Bielsko-Biała Theatres - Halina Łapińska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Culture is one of the most essential development factors influencing the quality of life and social advancement. Financing of cultural institutions from public funds aims at propagation of culture, supporting artists and artistic work, as well as national heritage. The group of entities involved in cultural activities include numerous public institutions, non-governmental organisations and private individuals. Local government units play a key role in this field. The paper seeks to examine the importance of city budget grants for the existence of theatres. The adopted theory that the city budget grant is significant for the functioning of theatres was confirmed by the analysis of the revenues of Bielsko-Biała theatres, however the share of local government subsidies in total revenues of theatre institutions seems to be on the decrease.